Development of A Peer Assessment Scientific Attitude Assessment Instrument on Learning Short Story Texts of Class XI Students at State Senior High School 1 Kualuh Hilir - Hanifah Sitorus Pane; Syahnan Daulay; M. Oky Ferdian Gafari (BIRCU, 2019)
Peer assessment is a form of assessment of a student towards other students. In peer assessment, students are involved directly in the assessment process. The aim is to develop of a peer assessment scientific attitude assessment instrument on learning short story text of XI students at State Senior High School 1 Kualuh Hilir. Methodology of this research uses quantitative and to find the results of the development research presented in this discussion are, describing the process of developing a scientific assessment instrument based on peer assessment, describing the feasibility of peer assessment based scientific attitude assessment instruments, describing the results of testing instruments for evaluating students' scientific attitudes based on peer assessment in short story text learning.